Medical consumerism in the UK, from 'citizen's challenge' to the 'managed consumer'-A symbol without meaning? - Steve Iliffe; Jill Manthorpe (Wiley, 2021)
Abstract Background In Britain's National Health Service (NHS), medical consumerism is disliked by many doctors but managed by NHS leaders. Managed consumers have choices about treatment options, but are expected to help contain costs, improve quality of care, take part in clinical research and advocacy, and increase productivity. There are so many meanings for medical consumerism that it can be categorized, in post‐structuralist terms, as a 'symbol without meaning', but meanings are plentiful in the NHS. Policy expectations Choices made by discriminating consumers were expected to improve the quality of medical care for all. Extending choice to the many, and not restricting options to the few, would allow gains from choices to accumulate, so that choice would sustain social solidarity. Managed consumerism would in theory, therefore, instil reasonable choices and responsible behaviours in a moralized citizenry, across the nation. The advocates of New Labour's espousal of medical consumerism expected the accumulative effects of customer choices to challenge professional and occupational power, erode the medical model of health and illness, constrain professional judgements, and open the NHS to new ways of working. Almost all their expectations have been thwarted, so far. Conclusions Managed consumerism is far from being a meaningless symbol. This discussion paper explores the territory of managed consumerism and suggests realistic ways to make it more effective in shaping the NHS. Patient & Public Contribution We developed the arguments in this discussion paper with insights provided by a lay expert (see Acknowledgements) with experience of consumerism in both public sector management and a disease‐related charity.